Revisiting Culture: Reforming Christian Cultural Identity - Widjaya, Yesaya Adhi (Universitas Pelita Harapan, 2025)
This paper discusses the impact of Christianity on today’s culture, so it is written from a Christian perspective. Culture, whether we realize it or not, has a powerful impact on human life. It shapes people's worldview, thinking patterns, life habits, goals, pursuits, choices, and desires. This paper aims to recall the engagement and activeness of Christians in culture, for if not, then Christianity will not have any impact in people's lives, rather it is the world that will influence and shape Christianity. The method used is a literature review, specifically the fine and incisive literatures on the cultural engagement of Christianity. This discussion of cultural engagement will use a four-question structure: